Users' information behaviour - a gender perspective - Jela Steinerová; Jaroslav Susol (Information Research: An International Electronic Journal, 2007)
Introduction. The paper is based on the study of library users in Slovakia as part of a larger research project on the use of information. Method. A large-scale questionnaire survey was conducted in 2002 in sixteen academic and research libraries with 793 subjects, especially students and educators. Analysis. The data were analysed with the use of statistical package SPSS. Gender differences are analysed with regard to ways of information seeking, use of electronic resources and publishing. Results. Results indicate that men prefer individual information seeking and women apply collaborative information use. By sorting user types it was found out that women tended to manifest a pragmatic way of information use (the S type). Men confirmed analytic information processing (the A type). Women declared less experience in the use of electronic resources and publishing. Differences in orientation, collaboration and feelings have been noted. Conclusion. Gender as a variable can be productive for better understanding of cognitive and social background of human information processing. Findings can inform design of services and systems and information literacy policies.